(untitled) (Vietnam Journal of Community Medicine, 2022)
Hypertension is a chronic non-communicable disease that should be managed in the community and can be incorporated into the management process. Objective: To evaluate the management of hypertensive patients in some wards in Bac Tu Liem District, Hanoi city in 2017. Subjects: 185 hypertensive patients. Methods: Cross section, description. Results: Locally managed hypertensive patients were mainly over 60 years old, accounting for 84.7%, the group under 40 had no patients. Among managed patients, health insurance paid up to 92.2%. Among 185 hypertensive patients, the number of patients who want to be managed and dispensed drugs at the hospital is 59.9%, 29.3% at the medical station, 7% at the health center, and 3.8% at home. Locally managed hypertensive patients have basic knowledge about risk factors and their consequences, how to recognize and treat the disease. Patients with hypertension continue to have needs for management and treatment at health stations and are provided with information about the disease in the following forms: via television, ward radio, handouts and medical staff. Conclusion: The management of hypertension at health level should be paid more attention and attention.